(untitled) (Móin-Móin Magazine - Studies in the Art of Puppetry, 2023)
This article aims to reflect on the role of contemporary museums, thought from the formation of collections. Its perspective is to think the collections from their mediations and the transits of meanings, which occur in the time and space in which they are stored, treated, and communicated. From this perspective, it establishes the premise that museums and collections serve vital purposes when put into performance, in a given mise-en-scéne. To support the discussion, the text encompasses four axes of analysis, in the form of acts, which are: what they think of museums and what I think of museums; the collections and the sense of things; the museum for vital purposes, structured from some experiments of the author; and finally, it opens ways to think about the potential of the Tribo de Atuadores Ói Nóis Aqui Traveiz when designing a museum.